A Pride of Lions: Noel Paton and the National Wallace Monument. Issue 1 (November 2014) - Smailes, Helen E.
Abstract : In January 1859 the Scottish figure painter Joseph Noel Paton attempted a breakthrough as a sculptor by entering the first design competition for the National Wallace Monument in Stirling. Backed by his fellow Royal Scottish Academician George Harvey, Paton's monumental sculptural design of the Lion and Typhon was selected. The ensuing public furore focused on the sculpture's aesthetic unsuitability to the Abbey Craig site, its ambiguous symbolism and, by inference, its probable referencing of heraldic grievances orchestrated by the National Association for the Vindication of Scottish Rights in the mid-1850s. By March 1859 the Monument committee had rescinded its original decision. Following the second competition in July 1859, the Glasgow architect J. T. Rochead (an unsuccessful competitor in the first round) secured the definitive architectural commission. This article explores the complex cultural and political environment which Paton and Rochead both had to negotiate.